African Union Great Green Wall Initiative Experts’ and Partners’ Engagement Meeting Report (13th-15th May 2025) - Africa Union; Accelerating Impacts of CGIAR Climate Research for Africa (2025)
This report provides a summary of the African Union (AU) Great Green Wall Initiative (GGWI) Experts’ and Partners’ Engagement Meeting. The meeting was held from the 13th - 15th May 2025 at the AU Headquarters in Addis Ababa, Ethiopia. The purpose of the meeting was to foster collaboration and coordination among key stakeholders to streamline implementation and operationalise the GGWI Strategy. The gathering provided a critical platform for organisations and relevant stakeholder groups to align their initiatives and enhance operational efficiencies.